Studies on land utilization for rural and urban stakeholders: A case study - KALSI, NAMRITA; KIRAN, RAVI (The Indian Journal of Agricultural Sciences, 2015)
This study attempts to understand the utilization of land for Development from the perspective of the stakeholder. A balanced economic development embracing rural or agriculture on one hand and urban or industrial growth on the other side, is indispensable for emerging economies like India. The present research is a study of the diverse objectives and how they can be attempted, with a least possible resistance or friction, through a medium of consultative approach. The results have been derived through a survey of stakeholders, covering land owners and other stakeholders through a case study of Greater Mohali Region of Punjab, primarily an agrarian state. The paper tries to throw light on recent evolving land legislatures and compare it with stakeholders options, preferences and incentives needed to facilitate land utilization for development. The results showed that stakeholders are less averse to spare land for certain key sectors like transport, social infrastructure like health and education. Not only this, the acceptance is more if the methodology is packaged through smooth processes, the approach is sensitive and incentivized with marketbased compensation.